Fabrication of Microlens Arrays with High Quality and High Fill Factor by Inkjet Printing. Issue 14 (13th June 2022) - Zhang, Qiaoshuang; Schambach, Maximilian; Schlisske, Stefan; Jin, Qihao; Mertens, Adrian; Rainer, Christian; Hernandez‐Sosa, Gerardo; Heizmann, Michael; Lemmer, Uli
Abstract: Microlens arrays (MLAs) have a variety of applications in, e.g., display systems, projection optics, and sensors. They can be manufactured by various fabrication methods. Among all, inkjet printing stands out because it offers a straightforward, versatile, and low‐cost fabrication route. However, extra manufacturing steps such as photolithography are so far involved to pre‐structure the substrate in order to improve the uniformity of the printed MLAs and achieve a high fill factor (FF). In this study, the fabrication of MLAs is reported on unstructured substrates by inkjet printing using an optimized UV‐curable ink on top of self‐assembled monolayers (SAMs). The latter allows for tuning the surface free energy and thus the aspect ratio of the microlenses. The high uniformity of the printed MLAs is demonstrated by the automatic quantitative evaluations, where the standard deviations of the radii are below 2.5% and of the sag heights are less than 3.9%. An unprecedented FF of 88% amongst all inkjet‐printed MLAs on unstructured substrates is achieved. Digitally controlled large area fabrication is demonstrated, both, on rigid as well as on flexible substrates, opening a pathway for customized microoptics by additive manufacturing. Abstract : The microlens arrays (MLAs) with a high fill factor (FF), excellent uniformity, and high‐quality imaging performance are fabricated by inkjet printing. With an optimized ink and by using self‐assembled monolayers, tunable and cost‐effective fabrication of MLAs is demonstrated with a high FF and excellent optical quality.